Finite element analysis of internal winding faults in distribution transformers. - Wang, H. (IEEE Transactions on power delivery)
With the appearance of deregulation, distribution transformer predictive maintenance is becoming more important for utilities to prevent forced outages with the consequential costs. To detect and diagnose a transformer internal fault requires a transformer model to simulate these faults. This paper presents finite element analysis of internal winding faults in a distribution transformer. The transformer with a turn-to-earth fault or a turn-to-turn fault is modeled using coupled electromagnetic and structural finite elements. The terminal behaviors of the transformer are studied by an indirect coupling of the finite element method and circuit simulation. The procedure was realized using a commercially available software. The normal case and various faulty cases were simulated and the terminal behaviors of the transformer were studied and compared with field experimental results. The comparison results validate the finite element model to simulate internal faults in a distribution transformer.